Visualizing Intramyocardial Steam Formation with a Radiofrequency Ablation Catheter Incorporating Near‐Field Ultrasound. (25th July 2013) - WRIGHT, MATTHEW; HARKS, ERIK; DELADI, SZABOLCS; FOKKENROOD, STEVEN; ZUO, FEI; VAN DUSSCHOTEN, ANNEKE; KOLEN, ALEXANDER F.; BELT, HARM; SACHER, FREDERIC; HOCINI, MÉLÈZE; HAÏSSAGUERRE, MICHEL; JAÏS, PIERRE
Visualizing Steam Pops Introduction Steam pops are a risk of irrigated RF ablation even when limiting power delivery. There is currently no way to predict gas formation during ablation. It would be useful to visualize intramyocardial gas formation prior to a steam pop occurring using near‐field ultrasound integrated into a RF ablation catheter. Methods and Results In an in vivo open‐chest ovine model (n = 9), 86 lesions were delivered to the epicardial surface of the ventricles. Energy was delivered for 15–60 seconds, to achieve lesions with and without steam pops, based on modeling data. The ultrasound image was compared to a digital audio recording from within the pericardium by a blinded observer. Of 86 lesions, 28 resulted in an audible steam pop. For lesions that resulted in a steam pop compared to those that did not (n = 58), the mean power delivered was 8.0 ± 1.8 W versus 6.7 ± 2.0 W, P = 0.006. A change in US contrast due to gas formation in the tissue occurred in all lesions that resulted in a steam pop. In 4 ablations, a similar change in US contrast was observed in the tissue and RF delivery was stopped; in these cases, no pop occurred. The mean depth of gas formation was 0.9 ± 0.8 mm, which correlated with maximal temperature predicted by modeling. Changes in US contrast occurred 7.6 ± 7.2 seconds before the impedance rise and 7.9 ± 6.2 seconds (0.1–17.0) before an audible pop. Conclusion Integrated US in an RF ablation catheter is able to visualize gas formation intramyocardially several seconds prior to a steam pop occurring. This technology may help prevent complications arising from steam pops.